Penanaman Nilai-Nilai Karakter dalam Pembelajaran Pendidikan Pancasila dan Kewarganegaraan di Madrasah Aliyah Muhammadiyah Klaten - Sayektiningsih, S.; Sumardjoko, Bambang; Muhibin, Achmad (Manajemen Pendidikan, 2017)
This study attempts to described in detail and clear about planting value character inlearning education Pancasila and Citizenship covered planning, the implementationof the, assesment, obstacles faced and a solution that attempts at constraints. The kindof research qualitative with the design case study. The research phase in MadrasahAliyah Muhammadiyah Klaten. Technique data collection with the methods interview,observation and study the contents of doecumentation, with informants students,teachers, head madrasah, deputy head of madrasah affairs curriculum , and theother related. Technique data analysis model interactive (display at the interactivemodel of analysis), validity data using a method of triangulation source. Theresults of research is planting the values of the character in the learning educationPancasila and Citizenship in Madrasah Aliyah Muhammadiyah Klaten that havebeen carried out with an implement the theory of learning involving planning oflearning, the implementation of interactive learning, evaluation which includes theaspect of the attitude (affective), the aspect of knowledge (cognitive), and aspectskill (psichomotoryc). Also some berriers faced in the planting the values of goodcharacter from students in the form of the nature of character of students that lazybum, the influence of students as well as from a teacher in the form of limitationsin designing lesson plans, make use of technology and the source or a mediumthat variatif as well as the curriculum. A solution which is being undertaken to theresistance of the student with the approach in the form of psichologis, assistance,the guidance and his exemplary, include students in axtracurricular activities andorganization of Muhammadiyah, gifts (reward) and punishment. While solution forteachers by involving in training 2013 Curriculum, MGMP and well as counsellingit.